Perkembangan Pelabuhan Perikanan Nusantara Kejawanan dan Kontribusinya terhadap Pemberdayaan Sosial Ekonomi Masyarakat Nelayan Kota Cirebon, 1994-2011 - Juhaeriyah Juhaeriyah; Singgih Tri Sulistiyono; Alamsyah Alamsyah (Diponegoro University, 2018)
This article aims to analyze the development of the Fishing Port and its contribution to the economic life of fishing communities at Cirebon in 1994-2011. The Fisheries Port of the Surgeon was built in 1994 and began operating in 1997 with trial status. Then in 1999, the Cirebon fishing port status changed to the Nusantara Fisheries Port (PPN). PPN equipped with basic, functional, and supporting facilities that aim to support port activities. The basic facilities available in PPN Vocational consist of trapezoidal breakwaters. Meanwhile, the technical facilities available at PPN included administrative offices, Fish Auction Places (TPI), ice warehouses, water reservoirs, water networks equipped with water pumps, meters, and pipe installations that reach the port dock, as well as electricity networks. Besides, PPN also had supporting facilities consisting of security posts, mosques, bathrooms, and official homes. In its development, PPN Kejawanan had a significant contribution in the socio-economic empowerment efforts of fishing community at Cirebon. Those efforts were included in empowering women at households level and fostering the fishermen to increase welfare and employment opportunities.